2018
DOI: 10.3390/nu10081033
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index and Biomarkers of Lipoprotein Metabolism, Inflammation and Glucose Homeostasis in Adults

Abstract: Accumulating evidence identifies diet and inflammation as potential mechanisms contributing to cardiometabolic risk. However, inconsistent reports regarding dietary inflammatory potential, biomarkers of cardiometabolic health and metabolic syndrome (MetS) risk exist. Our objective was to examine the relationships between a food frequency questionnaire (FFQ)-derived dietary inflammatory index (DII®), biomarkers of lipoprotein metabolism, inflammation and glucose homeostasis and MetS risk in a cross-sectional sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
125
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 144 publications
(140 citation statements)
references
References 51 publications
9
125
6
Order By: Relevance
“…Regular physical activity and replacement of sedentary behaviour with moderate to vigorous physical activity have been associated with more favourable inflammatory profiles in adults . On the other hand, adverse lifestyle habits such as smoking and alcohol consumption have been linked with elevated inflammatory status and more pro‐inflammatory diets, in line with our findings. Specific nutrients also are considered to be anti‐inflammatory, such as fibre, folate and vitamins E and C .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regular physical activity and replacement of sedentary behaviour with moderate to vigorous physical activity have been associated with more favourable inflammatory profiles in adults . On the other hand, adverse lifestyle habits such as smoking and alcohol consumption have been linked with elevated inflammatory status and more pro‐inflammatory diets, in line with our findings. Specific nutrients also are considered to be anti‐inflammatory, such as fibre, folate and vitamins E and C .…”
Section: Discussionsupporting
confidence: 90%
“…8,9 The literature-derived Dietary Inflammation Index (DII ® ) was developed to characterize the inflammatory potential of an individual's diet on a spectrum from anti-to pro-inflammatory. 10 The DII, which is validated against several inflammatory biomarkers in numerous populations, 11,12 including an Irish adult cohort, 13 has been associated with a range of health outcomes including cancer, asthma, anthropometric measures, cardiometabolic health, metabolic syndrome (MetS) and adverse mental health outcomes. [14][15][16] Although less well-studied in pregnancy, the DII score positively correlates with interval changes in high-sensitivity CRP during pregnancy.…”
mentioning
confidence: 99%
“…Neufcourt et al reported that there was no significant relationship between WC and DII 21 , which was inconsistent with the results of the present study. On the other hand, some studies have shown contradictory results 22,25,26 . The relationship between WC and DII can be interpreted as follows; Since the WC measures abdominal obesity, it can have an important role in the prediction of inflammatory factors 41 .…”
Section: Discussionmentioning
confidence: 99%
“…more negative) E-DII scores indicate more anti-inflammatory diets. The E-DII score has been construct validated and consistently associated with elevated inflammatory biomarker levels such as IL-6 (27) , TNF-α (27) and C-reactive protein (28) .…”
Section: Energy-adjusted Dietary Inflammatory Index Score Calculationmentioning
confidence: 99%